2016
DOI: 10.21003/ea.v160-15
|View full text |Cite
|
Sign up to set email alerts
|

Impact of women in the board of directors on business risk of Vietnamese firms

Abstract: Abstract. This article aims at assessing the influence of women in the board of directors (BOD) on risk management in Vietnamese firms. The study touches upon a sample of 284 companies listed on the HOSE (Ho Chi Minh City Stock Exchange -Vietnam) in the period of [2008][2009][2010][2011][2012][2013][2014]. Their data was regressed by the random effects model (REM) and the fixed effects model (FEM). To find out which method is the most appropriate, we used the Hausman test. The study clarifies women's role in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
3
1
Order By: Relevance
“…The study could not find any significant impact of FCEO and FDG on RTB. These outcomes are inconsistent with past studies [34][35][36][37][38]. Hence, H1b is partially accepted.…”
Section: Impact Of Femininity On Firm Risk-takingcontrasting
confidence: 75%
See 2 more Smart Citations
“…The study could not find any significant impact of FCEO and FDG on RTB. These outcomes are inconsistent with past studies [34][35][36][37][38]. Hence, H1b is partially accepted.…”
Section: Impact Of Femininity On Firm Risk-takingcontrasting
confidence: 75%
“…Refs. [35][36][37][38] showed a negative effect of female CEO on RTB, and [35] found a positive effect of female CEO on FSTB.…”
Section: Empirical Reviewmentioning
confidence: 92%
See 1 more Smart Citation
“…This study found that only 37 percent of the sample firm years have a woman on their boards, and only 23 percent of the firm years have independent woman directors. From the analysis of recent literature, it has been found that, in order to realize significant contributions from a gender diverse board, an average of 30 percent female representation has to be attained (Kanter, 1977; Do et al , 2016; Ben-Amar et al , 2017; Kramaric and Miletic, 2017; Rossi et al , 2017; Strydom et al , 2016). The findings suggest that merely mandating the presence of one woman on each corporate board is not sufficient in an emerging economy like India.…”
Section: Discussionmentioning
confidence: 99%